Public Perception of AI Dubbing Technology Implementation on The SripokuTV Youtube Channel - Rizka Pratiwi Utami; Budi Santoso; Arif Ardiansyah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to analyze public perception in Palembang City toward the use of Artificial Intelligence (AI)-based dubbing technology on the SripokuTV YouTube channel. The research employs a quantitative approach using a survey method involving 100 respondents selected through purposive sampling. Data were collected through an online questionnaire and analyzed using descriptive statistics and a Likert scale. The findings indicate that public perception tends to be positive, with an average index score of 83.86% (agree category). AI dubbing technology is considered beneficial, easy to use, and capable of improving audience comfort and information comprehension. However, several limitations remain, particularly in terms of intonation, emotional expression, and the naturalness of the generated voice. Despite these limitations, the level of public trust in the credibility of the information remains high. This study concludes that AI dubbing technology is feasible to be implemented in digital media and has strong potential for further development, especially with improvements in technical quality and strengthening of ethical and transparency aspects.